Evaluation of Learners’ Academic Performance in Teaching and Learning Civil Engineering During the COVID-19 Pandemic - Md Nujid, Masyitah; Tholibon, Duratul Ain (International Journal of Engineering Pedagogy, 2023)
Panic due to COVID-19 has disrupted teaching and learning session all over the world—refraining teachers and students from primary, secondary and tertiary education levels from attending physical classes in the traditional way. However with emergency circumstance without proper planning and action in delivering their subject matter, has given huge impacts on academic performance to educators and learners in identifying teaching and learning methods during the time. This study evaluates the academic performance of learners for specific course at the school department of university XXXX during COVID-19 pandemic using open and distance learning. The impacts of delivering in teaching and learning of the course contents through preference approach and use of digital communication technologies on learners’ academic performance during the time were studied. Case study method was used to evaluate the learners’ academic performance. Quantitative data were analyzed using descriptive statistics and thematic analysis was used to evaluate the qualitative data. Results of the analysis revealed that during open and distance learning, the learners’ preferred asynchronous method with WhatsApp social media platform chosen as the medium for communication between educators and learners. The findings show the learners are able to perform well in the course assessments despite the pandemic.